The urgency of evidence in psychotherapy - Alvaro Paredes-Rivera (Interacciones)
Currently, and after a long history of development and evolution, psychotherapy is a field where different models of intervention meet together, and everyone wants to obtain its own recognition and promotion. Considering this, it is contemplated the problem with the usefulness of the models and if them really present results, making the urgency of have an efficacy indicator of the treatments in use. In that sense, an important advance was the consolidation of the Efficacy of Psychological Treatments (Chambless & Hollon, 1998), and even more important the target of establish an Evidence-based Clinical Psychology (Spring, 2007). In this paper, it is made an analysis and review of this proposal, emphasizing the need of adopt it supporting the coherence with the idea of psychology as a science. What is more, it is described the criticism or the limitations of this point of view and some informed responses to them, considering the future challenges in the advance of clinical psychology and psychotherapy.